Perlindungan Hukum Musisi atas Hak Cipta dalam Royalti Berdasarkan Undang-Undang Hak Cipta di Indonesia - Willy Setiaza Permana; Anugrah, Dikha; Bias Lintang Dialog (Universitas Kuningan, 2025)
The growth of the music industry in Indonesia has led to disputes over works within the industry. This study aims to examine the regulation of royalties on music copyrights and the legal protection for musicians regarding copyright in royalty payments based on Law Number 28 of 2014 on Copyright. The research employs a descriptive-analytical approach with a juridical-normative method, involving literature studies and field studies. Data collection techniques include primary and secondary data sources, with literature studies serving as the primary tool for gathering information related to the research topic. The findings indicate that musicians holding copyright to their songs are not yet fully protected under the law, particularly concerning economic and moral rights, despite the existence of Government Regulation Number 56 of 2021. Preventive legal protection efforts include copyright registration, Law Number 28 of 2014, and the role of Collective Management Organizations. Copyright registration serves as concrete legal evidence in disputes. Repressive legal protection through the Commercial Court is regulated under the Copyright Law as a means of safeguarding musicians' exclusive rights, ensuring economic rights, and upholding human rights.